Note From the Editors: An Introduction to the IslandWood Papers on Social Work Innovation. (March 2017) - Traube, Dorian E.; Rice, Eric
In 2015, the University of Southern California School of Social Work convened the Social Work Innovation Roundtable with the goal of rigorously discussing the role of innovation in social work science and research. We convened a group of senior scholars in the field of social work along with emerging scholars (doctoral students and early career professors or researchers) to debate the practice of innovation, the nature of innovation, and how innovation may move social work forward. We posed the following questions to presenters and discussants: (1) Is innovation the enemy of science? (2) Does innovation have a role in science? and (3) Are innovation and scientific ideas simply different? During the course of 2 days, we argued over different perspectives on science and innovation with our colleagues. Out of those debates, this special issue of Research on Social Work Practice emerged.